INTERNATIONAL HUMAN RESOURCE MANAGEMENT AND LABOUR RELATIONS IN DEVELOPING HUMAN RESOURCES INDONESIA-JAPAN (TECHNICAL INTERN TRAINING PROGRAM) - Mohd. Heikal; Wanda Aditya Saputra; Wenny Wardianingsih Hsb; Miranda Syahputri; Ramadhania (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research aims to find out and describe about international human resource management and labour relations in developing human resources Indonesia-Japan TITP (Technical Intern Training Program). In his research, the type of research methods used in thi research in decriptive. Data collection thecnicues used is a review of the literatur or literature studies using data from books, documents, journals, and data analysis technique used is qualitativ data analysis technique. The results of studiey is in IHRM, the organizations competitive strategy. This srategy is developed in two ways: 1. Proactively, as a proactive strategy to address expected market forces. 2. Reactively, in reaction to the market conditions, the organization is facing. In the majority of businesses, a combination of these forces leads to the development of strategies. Indicate that the form of cooperation between Indonesia and Japan is funcional cooperation.even though Japan is the initiator country in this case study in the formation of this TITP program, there are interests between the two countries that need one another. Through the tranfer of skills helped by proffessionals, the goal of this collaboration is to accept young employees from developing nation nation as job training participans in the Japanese industry whitin a set time frame. With the objective of creating human resources that can contributions to the industrial economyof the nation.